Pengaruh Pengetahuan Akuntansi, Modal Usaha, dan Lama Usaha terhadap Keberhasilan Usaha UMKM di Kecamatan Tandes, Kota Surabaya - Surenggono Surenggono; Lilik Mardiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of accounting knowledge, business capital, and business length on the success of micro, small, and medium enterprises (MSMEs) in Tandes District, Surabaya City. The background of this research is based on the importance of financial management skills, sufficient capital availability, and business experience in supporting the sustainability and growth of MSMEs. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to MSME actors who are registered and domiciled in Tandes District. The sample criteria include fostered MSME actors who have been running their businesses for at least three years and marketing their own products. The number of respondents who were successfully collected in this study was 105 people. The data analysis technique used was multiple linear regression analysis with the help of SPSS software version 23.0. The results of the study show that the variables of accounting knowledge, business capital, and business duration simultaneously or partially have a positive and significant effect on the success of MSME businesses in Tandes District. Accounting knowledge helps business actors in managing finances and recording transactions systematically. Adequate business capital is an important factor in business development and increasing production capacity. Meanwhile, the length of the business reflects the accumulation of experience and practical knowledge that can improve managerial efficiency and effectiveness. Thus, these three variables have a strategic role in increasing the success of MSMEs. This finding provides an implication that MSME empowerment programs should be focused on improving accounting literacy, wider access to capital, and long-term business assistance. Local governments and related institutions can take these results into consideration in designing policies that support the sustainable growth of MSMEs.